Effectiveness of powered exoskeleton use on gait in individuals with cerebral palsy: A systematic review. - Lucinda Rose Bunge (Public Library of Science (PLoS), 2021)
Background Cerebral palsy (CP) is a leading cause of childhood disability. The motor impairments of individuals with CP significantly affect the kinematics of an efficient gait pattern. Robotic therapies have become increasingly popular as an intervention to address this. Powered lower limb exoskeletons (PoLLE) are a novel form of robotic therapy that allow the individual to perform over-ground gait training and yet its effectiveness for CP is unknown. Purpose To determine the effectiveness of PoLLE use on gait in individuals with CP. Method A systematic search of eight electronic databases was conducted in March 2020. Studies included children (0-18 years) and or adults (18+ years) diagnosed with CP who used a PoLLE for gait training. This review was conducted and reported in line with the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) statement, with the methodology registered with PROSPERO (CRD42020177160). A modified version of the McMaster critical review form for quantitative studies was used to assess the methodological quality. Due to the heterogeneity of the included studies, a descriptive synthesis using the National Health & Medical Research Council (NHMRC) FORM framework was undertaken. Results Of the 2089 studies screened, ten case series and three case studies met the inclusion criteria highlighting the current evidence base is emerging and low level. A range of PoLLEs were investigated with effectiveness measured by using a number of outcome measures. Collectively, the body of evidence indicates there is some consistent positive evidence on the effectiveness of PoLLE in improving gait in individuals with CP, with minimal adverse effects. While this is a positive and encouraging finding for an emerging technology, methodological concerns also need to be acknowledged. Conclusion With rapidly evolving technology, PoLLEs could play a transformative role in the lives of people impacted by CP. Ongoing research is required to further strengthen the evidence base and address current methodological concerns.